Public justice and the criminal trial in late medieval Italy : Reggio Emilia in the visconti age - Vitiello, Joanna Carraway (2016)
This book examines the administration of justice in the small northern Italian town of Reggio Emilia at the end of the fourteenth century. It seeks to add to the discussion on dispute resolution and court processes in late medieval Europe, moving the focus outside the major urban centers of late medieval Italy to the periphery of urban life.